The politics of nation building and citizenship in Singapore - Hill, Michael, 1943 December 30- (Politics in Asia series., 1995)
Since independence in 1965 Singapore has strengthened its own national identity through a conscious process of nation-building and promoting the active role of the citizen within society. Singapore is a state that has firmly rejected welfarism but whose political leaders have maintained that collective values, instead of those of autonomous individuals, are essential to its very survival. The book begins by examining basic concepts of citizenship, nationality and the state in the context of Singapore's arrival at independence. The theme of nation-building is explored and how the creation of.